PENGARUH MASA KERJA DAN PENDIDIKAN GURU TERHADAP KINERJA GURU SDN SUKABUMI 10 KOTA PROBOLINGGO - Hasan, Rohmat (Jurnal Penelitian dan Pendidikan IPS, 2017)
This research aims to know the influence of years of service and educational background on teachersÃ¢â‚¬â„¢ working performance at SDN Sukabumi 10 Probolinggo. Ã‚Â Forty (40) students were invoked in this research as respondents. As a result, it showed that there was significant influence of years of service, educational background, and years of service and educational background simultaneously on teachersÃ¢â‚¬â„¢ working performance at SDN Sukabumi 10 Probolinggo.